2008
DOI: 10.1111/j.1478-3231.2007.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of a covered vs. uncovered transjugular intrahepatic portosystemic shunt in Budd–Chiari syndrome

Abstract: A transjugular intrahepatic portosystemic shunt using PTFE-covered stents shows better patency rates than bare stents in BCS. Moreover, TIPS leads to an improvement in important prognostic indicators for the survival of patients with BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 19 publications
2
19
2
2
Order By: Relevance
“…The present series includes only patients treated with bare stents for the TIPS creation and none treated with PTFE-covered stents positioning. Although it has been suggested that PTFE-covered stent may improve the outcome of patients treated with TIPS, due to a reduction of stent dysfunctions and to improved long-term primary stent patency, the survival rate of patients in the present study only employing bare stents is comparable to that of previous series using covered stents [21][22][23][24][25] as well as the TIPS patency rates, with cumulative primary and secondary patency rates, respectively, 79% and 99% at a mean of 30 months, similarly to those reported by other authors [5]. Moreover, the number of enrolled patients in this study is modest, due to the restricted criteria for TIPS placement in our center; this issue could lead to an overfitted multivariate analysis and low power of subsequent analyses (Kaplan-Maier curves).…”
Section: Discussionsupporting
confidence: 80%
“…The present series includes only patients treated with bare stents for the TIPS creation and none treated with PTFE-covered stents positioning. Although it has been suggested that PTFE-covered stent may improve the outcome of patients treated with TIPS, due to a reduction of stent dysfunctions and to improved long-term primary stent patency, the survival rate of patients in the present study only employing bare stents is comparable to that of previous series using covered stents [21][22][23][24][25] as well as the TIPS patency rates, with cumulative primary and secondary patency rates, respectively, 79% and 99% at a mean of 30 months, similarly to those reported by other authors [5]. Moreover, the number of enrolled patients in this study is modest, due to the restricted criteria for TIPS placement in our center; this issue could lead to an overfitted multivariate analysis and low power of subsequent analyses (Kaplan-Maier curves).…”
Section: Discussionsupporting
confidence: 80%
“…The development of covered stents, however, has significantly improved the patency of TIPS in BCS (53,54). Rossle et al (58) achieved initial success in 33 of 35 patients with 1-and 5-year transplant-free survival rates of 93% and 74%, respectively.…”
Section: Transjugular Intrahepatic Portosystemic Shunt (Tips) and Surmentioning
confidence: 99%
“…TIPS is also recommended for those with the acute form of BCS who failed to respond to thrombolytic therapy (2,37). TIPS is the most common intervention for BCS in Europe, and many studies have reported its high success rate and relatively low rate of complications (52)(53)(54)(55).…”
Section: Transjugular Intrahepatic Portosystemic Shunt (Tips) and Surmentioning
confidence: 99%
“…In all of these patients, the end of the stent did not extend into the IVC, which is a possible explanation for the stenosis. Nevertheless, the rates of TIPS dysfunction were lower than those in larger previous studies [7][8][9]18], which could be explained by the use of polytetrafluoroethylene-covered stents as these have been proven to be more patent than bare metal stents [7,8,19,20]. As the BCS-TIPS PI score is considered a predictor of TIPS failure, the recommendations for patients with high scores is to consider liver transplantation instead of TIPS [15].…”
Section: Discussionmentioning
confidence: 92%